Chronic activation of the innate immune system may underlie the metabolic syndrome - Duncan, Bruce Bartholow; Schmidt, Maria Inês (São Paulo Medical Journal, 2001)
CONTEXTO: The metabolic syndrome is characterized by a clustering, in free-living populations, of cardiovascular and diabetes risk factors generally linked to insulin resistance, obesity and central obesity. Consonant with the well-established inflammatory pathogenesis of atherosclerotic disease, the metabolic syndrome is now being investigated in relation to its inflammatory nature. OBJETIVO: We present cross-sectional findings demonstrating that markers of inflammation correlate with components of the metabolic syndrome, and prospective findings of the ARIC Study indicating that markers of inflammation and endothelial dysfunction predict the development of diabetes mellitus and weight gain in adults. We present biological evidence to suggest that chronic activation of the innate immune system may underlie the metabolic syndrome, characterizing the common soil for the causality of type 2 diabetes mellitus and cardiovascular disease. CONCLUSIONS: Better understanding of the role of the innate immune system in these diseases may lead to important advances in the prediction and management of diabetes and cardiovascular disease.